2012
DOI: 10.1152/ajpendo.00599.2011
|View full text |Cite
|
Sign up to set email alerts
|

The calcium-sensing receptor complements parathyroid hormone-induced bone turnover in discrete skeletal compartments in mice

Abstract: The calcium-sensing receptor complements parathyroid hormone-induced bone turnover in discrete skeletal compartments in mice. Am J Physiol Endocrinol Metab 302: E841-E851, 2012. First published January 24, 2012; doi:10.1152/ajpendo.00599.2011.-Although the calcium-sensing receptor (CaSR) and parathyroid hormone (PTH) may each exert skeletal effects, it is uncertain how CaSR and PTH interact at the level of bone in primary hyperparathyroidism (PHPT). Therefore, we simulated PHPT with 2 wk of continuous PTH infu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 57 publications
2
21
0
1
Order By: Relevance
“…61 These findings seem to be consistent with a role for CaSR in augmenting PTHinduced bone formation in adults as well as in neonates.…”
Section: Effects In Adultssupporting
confidence: 74%
See 2 more Smart Citations
“…61 These findings seem to be consistent with a role for CaSR in augmenting PTHinduced bone formation in adults as well as in neonates.…”
Section: Effects In Adultssupporting
confidence: 74%
“…72 In addition, CaSR has been reported to modulate PTHstimulated bone turnover in 8weekold mouse models, in which PTH was infused in Pth -/-;Casr -/-mice. 61 In Pth -/-;Casr -/-mice, the increases in cortical porosity and decreases in cortical bone volume induced by PTH infusion were reduced in comparison with cortical bone changes induced by PTH in Pth -/-mice. 61 Additionally, PTH stimulated RANKL expression and osteoclastogenesis were lower in cultured bone marrow from Pth -/-;Casr -/-mice than PTH responses in cultured bone marrow from Pth -/-mice.…”
Section: Effects In Adultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Indeed, the continuous infusion of PTH, which mimics a state of primary hyperparathyroidism, increases cortical bone turnover and cortical porosity in PTH−/− but to a much lower extent in CaSR−/ −PTH−/−, indicating that CaSR mediates, at least in part, the effects of PTH on bone turnover [65].…”
Section: Casr-mediated Effects In Cultured Chondrocytesmentioning
confidence: 99%
“…Silver et al (109) demonstrated that HSCs express the calcium-sensing receptor (CaR), which is indispensable for niche spatial localization, and more recently, Adams et al (1) revealed that CaR is indispensable for the proper engraftment of HSCs within the endosteal niche that is rich in extracellular calcium. In addition, genetic deletion of CaR reduced PTH-stimulated bone turnover in trabecular bone and tended to impede PTH-induced increases in trabecular bone (145). Under normal physiological conditions, PTH plays a watchdog role for calcium homeostasis, and, further, PTH treatment provides stromal support for primitive hematopoietic cells (17,49).…”
Section: Pth Outcomes: Exploring "The Bright and The Dark Side Of Thementioning
confidence: 99%